Kundabuffer

Geometry Level 4

Two congruent circles are inscribed in a unit square A B C D ABCD . What is the length of E B EB ?

Submit 1 0 5 E B \lfloor{10^5\cdot{EB}}\rfloor .


The answer is 64779.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Oct 19, 2020

Let the radius of the congruent circle be r r and A E B = θ \angle AEB = \theta . The the length B C = 1 BC = 1 is given by:

r + r cot θ 2 + r cot ( 9 0 θ 2 ) + r = 1 r ( 2 + cot θ 2 + tan θ 2 ) = 1 Let t = tan θ 2 2 + 1 t + t = 1 r \begin{aligned} r + r \cot \frac \theta 2 + r \cot \left(90^\circ - \frac \theta 2\right) + r & = 1 \\ r (2 + \cot \frac \theta 2 + \tan \frac \theta 2) & = 1 & \small \blue{\text{Let }t = \tan \frac \theta 2} \\ \implies 2 + \frac 1t + t & = \frac 1r \end{aligned}

Similarly for A B AB :

r cot ( 4 5 θ 2 ) + r = 1 1 + t 1 t + 1 = 1 r \begin{aligned} r \cot \left(45^\circ - \frac \theta 2\right) + r & = 1 \\ \implies \frac {1+t}{1-t} + 1 & = \frac 1r \end{aligned}

Therefore.

2 + 1 t + t = 1 + t 1 t + 1 t 2 + t + 1 t = 1 + t 1 t ( 1 t ) ( t 2 + t + 1 ) = t + t 2 1 t 3 = t + t 2 t 3 + t 2 + t 1 = 0 \begin{aligned} 2 + \frac 1t + t & = \frac {1+t}{1-t} + 1 \\ \frac {t^2 + t + 1}t & = \frac {1+t}{1-t} \\ (1-t)(t^2 + t + 1) & = t + t^2 \\ 1 - t^3 & = t + t^2 \\ t^3 + t^2 + t - 1 & = 0 \end{aligned}

Solving for t t using Cardano's method , we get t = tan θ 2 = 17 27 + 11 27 3 + 17 27 11 27 3 1 3 0.543689013 t = \tan \frac \theta 2 = \sqrt[3]{\frac {17}{27}+\sqrt{\frac {11}{27}}} + \sqrt[3]{\frac {17}{27}-\sqrt{\frac {11}{27}}} - \frac 13 \approx 0.543689013 . Note that E B = cot θ = 1 t 2 2 t 0.647798871 1 0 5 E B = 64779 EB = \cot \theta = \dfrac {1-t^2}{2t} \approx 0.647798871 \implies \lfloor 10^5 \cdot EB \rfloor = \boxed{64779} .

Much better than mine. +1 +1 +1

Note that you don't need to compute t t in the middle of your calculation. Here's what I would have done:

Since we got 1 t 3 = t + t 2 1 - t^3 = t + t^2 , then 1 t 2 = t + t 3 E B = cot θ = 1 t 2 2 t = t + t 3 2 t = 1 + t 2 2 1 - t^2 = t + t^3 \implies EB = \cot \theta = \dfrac{1-t^2}{2t} = \dfrac{t+ t^3}{2t} = \dfrac{1 + t^2}2 .

And because we know that f ( X ) = X 3 + X 2 + X 1 = 0 f(X) = X^3 + X^2 + X - 1 = 0 has a root t t , then f ( X ) = 0 f(\sqrt X) = 0 has a root t 2 t^2 .

X X + X + X 1 = 0 X ( X + 1 ) = ( 1 X ) X ( X + 1 ) 2 = ( 1 X ) 2 X 3 + X 2 3 X 1 = 0 X \sqrt X + X + \sqrt X - 1 = 0\Rightarrow \sqrt X (X+1) = (1-X) \Rightarrow X(X+1)^2 = (1-X)^2 \Rightarrow X^3 + X^2 -3X - 1 = 0

The rightmost equation above has a root t 2 t^2 . By Cardano's method.... can you finish it off?

Pi Han Goh - 7 months, 3 weeks ago

Log in to reply

Got Cardano's done. Nice answer.

Chew-Seong Cheong - 7 months, 3 weeks ago

Let F F , G G , H H , J J be contact points as seen in the figure. Let K K , L L be the centers of the circles and M M the intersection of A E AE with J F JF . Denote K A F \angle KAF by θ \theta .

Then, K A G = θ \angle KAG=\theta , G K M = M L H = 2 θ \angle GKM=\angle MLH=2\theta .
Hence, we have

J F = J L + L M + M K + K F 1 = r + r cos 2 θ + r cos 2 θ + r cos 2 θ = 2 r 1 2 r ( 1 ) \begin{aligned} JF& =JL+LM+MK+KF \\ \Rightarrow 1 & =r+\dfrac{r}{\cos 2\theta }+\dfrac{r}{\cos 2\theta }+r \\ \Rightarrow \cos 2\theta & =\dfrac{2r}{1-2r} \ \ \ \ \ (1) \\ \end{aligned} Moreover, on K A F \triangle KAF ,

tan ( K A F ) = K F A F tan θ = r 1 r ( 2 ) \tan \left( \angle KAF \right)=\dfrac{KF}{AF}\Rightarrow \tan \theta =\dfrac{r}{1-r} \ \ \ \ \ (2) Furthermore, cos 2 θ = 1 tan 2 θ 1 + tan 2 θ ( 3 ) \cos 2\theta =\dfrac{1-{{\tan }^{2}}\theta }{1+{{\tan }^{2}}\theta } \ \ \ \ \ (3) .

Combining ( 1 ) (1) , ( 2 ) (2) and ( 3 ) (3) ,

2 r 1 2 r = 1 ( r 1 r ) 2 1 + ( r 1 r ) 2 4 r 3 8 r 2 + 6 r 1 = 0 \dfrac{2r}{1-2r}=\dfrac{1-{{\left( \dfrac{r}{1-r} \right)}^{2}}}{1+{{\left( \dfrac{r}{1-r} \right)}^{2}}}\Leftrightarrow \ldots \Leftrightarrow 4{{r}^{3}}-8{{r}^{2}}+6r-1=0 By Cardano's method , this cubic equation gives

r = 1 6 ( 4 2 3 33 17 3 + 3 33 17 3 ) 0.228155493653961 r=\frac{1}{6}\left( 4-\frac{2}{\sqrt[3]{3\sqrt{33}-17}}+\sqrt[3]{3\sqrt{33}-17} \right)\approx 0.228155493653961 Finaly, on E A B \triangle EAB ,

tan ( E A B ) = E B A B tan 2 θ = E B 1 E B = 2 tan θ 1 tan 2 θ E B = 2 r 1 r 1 ( r 1 r ) 2 E B = 2 r ( 1 r ) 1 2 r \tan \left( \angle EAB \right)=\frac{EB}{AB}\Rightarrow \tan 2\theta =\frac{EB}{1}\Rightarrow EB=\frac{2\tan \theta }{1-{{\tan }^{2}}\theta }\Rightarrow EB=\frac{2\frac{r}{1-r}}{1-{{\left( \frac{r}{1-r} \right)}^{2}}}\Rightarrow EB=\frac{2r\left( 1-r \right)}{1-2r} Substituting the value we found previously, we get E B 0.647798871261039 EB\approx 0.647798871261039 .
For the answer, 10 5 E B = 64779 \left\lfloor {{10}^{5}}EB \right\rfloor =\boxed{64779} .

Another exquisite answer. +1 +1 +1

Pi Han Goh - 7 months, 3 weeks ago

Log in to reply

Thanks a lot! I'm glad you liked it.

Thanos Petropoulos - 7 months, 3 weeks ago
Pi Han Goh
Oct 18, 2020

Let r r denote the radius of the two identical circles. And for simplicities sake, define 0 < h < 1 0<h<1 as the length E B EB .

The radius of the incircle of a triangle can be expressed as A = r s , A = r \cdot s, where A A denotes the area of the triangle, and s s as the semiperimeter of the triangle.

Let us focus on the bottom right-triangle, its area A A is simply h 2 \frac h2 . By Pythagorean theorem , the hypotenuse of this right-triangle is 1 + h 2 \sqrt{1+h^2} , and so its semiperimeter is s = 1 2 ( 1 + h + 1 + h 2 ) s = \frac12(1 + h + \sqrt{1+h^2}) . Thus, we can express r r in terms of h h alone.

A = r s r = A s = h 1 + h + 1 + h 2 A = rs \quad \Leftrightarrow \quad r = \frac As = \dfrac h{1 + h + \sqrt{1+h^2}}

Let us rotate the graph picture and plot these points on the Cartesian plane as such:

The equation of the straight line E A EA can be determined as y = h x + ( 1 h ) y = hx + (1-h)

And because the bottom left circle (it was previously a top right circle) is tangent to the x x -axis, y y -axis, and the straight line E A EA , the equation of this circle of radius r r satisfy ( x r ) 2 + ( y r ) 2 = r 2 (x - r)^2 + (y-r)^2 = r^2 . Substituting y = h x + ( 1 h ) y = hx + (1-h) , we get ( x r ) 2 + ( h x + 1 h r ) 2 = r 2 x 2 ( h 2 + 1 ) + x ( 2 r + 2 h ( 1 h r ) ) + ( 1 h r ) 2 = 0. (x-r)^2 + ( hx + 1-h-r)^2 = r^2 \quad\Leftrightarrow \quad x^2 (h^2 + 1) + x\big (-2r + 2h(1-h-r) \big) + (1-h-r)^2 = 0.

The above is a quadratic equation whose discriminant (in x x ) is 0, ( 2 r ) 2 4 ( h 2 + 1 ) ( 1 h r ) ( 2 h + ( 1 h r ) ) = 0. (-2r)^2 - 4(h^2 + 1)(1-h-r)(2h + (1-h-r)) = 0. Lastly, we substitute r = h 1 + h + 1 + h 2 r = \dfrac h{1 + h + \sqrt{1+h^2}} , and we can get 2 h 3 2 h 2 + 2 h 1 = 0 2h^3 -2h^2 + 2h - 1 = 0 . By Cardano's method , E B = h = 1 3 ( 1 32 13 + 3 33 3 + 13 + 3 33 4 3 ) 0.6477988. \Large EB = h = \frac13 \left( \, 1 - \sqrt[3]{\tfrac{32}{13 + 3 \sqrt{33}}} + \sqrt[3]{\tfrac{{13 + 3\sqrt{33}} }{{4}}} \, \right ) \approx 0.6477988. Hence, 1 0 5 E B = 64779 . \lfloor{10^5\cdot{EB}}\rfloor = \boxed{64779}.

Very nicely done. Did you make use of the discriminant being 0? Had you seen this one before?

Fletcher Mattox - 7 months, 3 weeks ago

Log in to reply

Yes, and no.

Pi Han Goh - 7 months, 3 weeks ago
Vinod Kumar
Nov 6, 2020

Let two circles radii equal to x, CE=b+x and EB=c+x. Write the following relations from figure

b+c+2x=1, on line CB

[(c-b)/2]^2+x^2=[(1/2)-x]^2, on tangent AE between two circles

(1-x+c)^2-(c+x)^2=1, on right triangle AEB

Solve with WolframAlpha, x=0.228155, c=0.419643,

EB=c+x=0.647799

Answer = 64779

Darn I put in the radius instead of EB

Sanchit Sharma - 2 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...